Informal incentives, labor supply, and the effect of immigration on wages - Matthias Fahn; Takeshi Murooka (Johannes Kepler University of Linz, Department of Economics, 2021)
This paper theoretically investigates how an increase in the supply of homogenous workers can raise wages, generating new insights on potential drivers for the observed non-negative wage effects of immigration. We develop a model of a labor market with frictions in which firms can motivate workers only through informal incentives. A higher labor supply increases firms' chances of filling a vacancy, which reduces their credibility to compensate workers for their effort. As a response, firms endogenously generate costs of turnover by paying workers a rent, and this rent is higher if an increase in labor supply reduces a firm's credibility. By this effect, a higher labor supply - for example caused by immigration - can increase workers' compensation. Moreover, an asymmetric equilibrium exists in which native workers are paid higher wages than immigrants and work harder. In such an equilibrium, an inflow of immigrants increases productivity, profits, and employment.
Keywords: D21; D86; F22; J21; J61; L22; 330; Informal Incentives; Labor Supply; Immigration